The return of the buffaloes : a Plains Indian story about famine and renewal of the earth - Goble, Paul. (Washington, D.C. : National Geographic Society, 1996)
Based on a Lakota legend in which a mysterious woman returns the buffalo and the other animals to the Indian people.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
4.8
3-6
Keywords: Famines -- Great Plains -- History -- Juvenile literature; Indians of North America -- Great Plains -- Folklore; Indians of North America -- Great Plains -- Food -- Juvenile literature; Folklore -- Great Plains; Indians of North America -- Great Plains -- Folklore; Teton Indians -- Folklore; Famines -- Great Plains -- History; Native Americans -- Great Plains -- Folklore; Native Americans -- Great Plains -- Food; Teton Indians -- Folklore